ANALISIS MODEL IDEAL STRUKTUR ORGANISASI KEPOLISIAN NEGARA REPUBLIK INDONESIA (POLRI) PASCAREFORMASI - Haryadi Mukhtas (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2019)
This study aims to formulate the ideal model of restructuring the National Police of Indonesia. The research design is descriptive qualitative, and data collection techniques include in-depth interviews, observation and documentation studies. The results of this study indicate that ideally, Polri organizations are of poor structural function. The structure is slim on Headquarters but strong at the regional level. Functional positions need to be reproduced in Headquarters, to be filled by middle officers with specific expertise. The type of organization needs to be changed from mechanical organization to organic through regional decentralization, so that the National Police of Indonesia is able to respond to problems and change the environment more quickly. Keywords: Restructuring; Bureaucratic Reform; Police Organization